Endoscopic Treatment of an Idiopathic Pancreaticopleural Fistula - Correia,João (2022)
Abstract A 61-year-old man was diagnosed with an exudative pleural effusion with raised amylase and bilirubin levels. The patient had no previous history of acute pancreatitis or trauma and no clinical or radiological signs of chronic pancreatitis. On thoracoabdominal computed tomography, a pancreatic pseudocyst with a pancreaticopleural fistula was identified. Endoscopic retrograde cholangiopancreatography identified a ductal disruption site in the body of the pancreas. Pancreatic sphincterotomy and stent placement in the duct of Wirsung, combined with medical management, allowed fistula closure, pseudocyst reabsorption, and no relapse of the pleural effusion. The relevance of this case lies not only in its rarity but also as it highlights the importance of a multidisci-plinary approach in such uncommon conditions. Optimal management of this condition is debatable due to the absence of prospective studies comparing medical, endoscopic, and surgical approaches.